2008
DOI: 10.3748/wjg.14.1182
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 2/Bv8 is expressed in Kupffer cells in liver and is down regulated in human hepatocellular carcinoma

Abstract: as expected. In addition, out of all isolated liver cells examined, only Kupffer cells (liver resident macrophages) express significant levels of PK2/Bv8 and its receptors, prokineticin receptor 1 and 2. CONCLUSION:In nor mal l ive r P K2/ B v8 a n d i t s receptors were specifically expressed by Kupffer cells. PK2/Bv8 expression decreased as the liver evolves t o wa r d s c a n c e r a n d d i d n o t c o r r e l a t e w i t h H C C angiogenesis. INTRODUCTIONIn vivo, a solid tumor can not progress beyond a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
2
22
0
Order By: Relevance
“…It is postulated that through this interaction they are key in instigating fibrosis following inflammation [93]. CD68+ KCs also co-express prokineticin 2/Bv8, a molecule strongly implicated in angiogenesis [43].…”
Section: Heterogeneitymentioning
confidence: 99%
“…It is postulated that through this interaction they are key in instigating fibrosis following inflammation [93]. CD68+ KCs also co-express prokineticin 2/Bv8, a molecule strongly implicated in angiogenesis [43].…”
Section: Heterogeneitymentioning
confidence: 99%
“…120 Because Bv8 expression is downregulated in hepatocellular carcinoma as compared to normal liver without correlation between expression levels of Bv8 and angiogenesis, further studies on the role of Bv8 in human cancer are warranted. 121 PlGF has been implicated in the resistance against anti-VEGF therapy. 122 Its levels correlate with clinical outcome in several, though not all human cancers.…”
Section: Gr1mentioning
confidence: 99%
“…We measured the expression of PROK1 and PROK2 in fresh human monocytes obtained from 10 different healthy donors and our results consistently showed very high expression of PROK2 but undetectable expression of PROK1 (data not shown). Furthermore, we recently showed that the resident macrophage population of human liver (called Kupffer cells) was the specific source of PROK2 in liver, whereas PROK1 was weakly expressed [25].…”
Section: Expression and Regulation Of Prokineticins And Prokineticin mentioning
confidence: 99%
“…Recently, we studied the expression of PROKR1 and PROKR2 in fresh human monocytes from 10 different donors at the protein level using flow cytometry and we observed that both receptors were expressed on the monocyte surface (J. Monnier, V. Quillien, C. Piquet‐Pellorce, C. Leberre, L. Preisser, H. Gascan & M. Samson, unpublished data). In addition, we showed that in liver hepatic cells both PROKR1 and PROKR2 mRNA were only expressed at high levels by Kupffer cells [25]. In mice peritoneal macrophages a predominance of PROKR1 transcripts was found, and macrophage cells extracted from PROKR1 knockout mice were unable to respond to PROK2 [29].…”
Section: Expression and Regulation Of Prokineticins And Prokineticin mentioning
confidence: 99%